Determinants of Inequality in Economic Development Between District/City in West Java Province 2017-2019 - Elvannyrossie, Asvira; Nurdany, Achmad (Department of Islamic Economics, Faculty of Islamic Economics and Business, Universitas Islam Negeri Sunan Kalijaga, 2024)
One of the ideals of a country is to create welfare for its citizens. For its welfare is the construction process. The development process, it requires the availability of natural resources and the condition of supportive human resources. These two aspects are very influential in development. However, the fact is that each region does not necessarily have this, or its conditions differ from other regions. So this triggers an increase or decrease in the level of development inequality. This study aims to analyze what factors influence the level of inequality in districts/cities in West Java in 2017-2019. This research is quantitative research with panel data sourced from the Central Statistics Agency of West Java Province with an annual span from 2017-2019 which includes 18 districts and 9 cities. The method used is a linear panel data regression with a fixed effect model. The dependent variable used is development inequality as measured by the Williamson index. Meanwhile, the dependent variable includes original local government revenue, agglomeration, mean years school, life expectancy, and labor force. The research results indicate that the dependent variable simultaneously affects development inequality. On a partial basis, the variables of local revenue, agglomeration have a positive and significant effect on inequality in economic development, while the variable life expectancy has a negative and significant effect on inequality in economic development. Meanwhile, the variables for the mean years school and the labor force have a positive but insignificant effect on the inequality of economic development between districts/cities in East Java Province.